Raltegravir‐emtricitabine‐tenofovir as HIV nonoccupational post‐exposure prophylaxis in men who have sex with men: safety, tolerability and adherence1. Issue 1 (6th September 2013) - McAllister, J; Read, P; McNulty, A; Tong, WWY; Ingersoll, A; Carr, A
<x xml:space="preserve">Abstract</x> Objectives Three‐drug nonoccupational post‐exposure prophylaxis (NPEP) typically includes co‐formulated emtricitabine‐tenofovir (FTC‐TDF) and a protease inhibitor. However, protease inhibitors can cause significant toxicities, can interact with prescribed and illicit drugs, and work late in the viral cycle. Agents that act before viral integration into host DNA may have efficacy advantages. Raltegravir (RAL) is a good candidate for NPEP as it has few side effects or drug interactions and acts prior to HIV integration. The objective of this study was to investigate the use of RAL in 3‐drug NPEP in terms of safety, adherence and tolerability. Methods We evaluated 28 days of RAL‐FTC‐TDF treatment in 86 men and FTC‐TDF treatment in 34 men eligible for three‐ and two‐drug NPEP, respectively. We assessed adherence (compared between groups and with nonstudy controls) and clinical and adverse events at weeks 1, 2 and 4, and efficacy at week 12. Analyses were by intention to treat, excluding from the adherence analysis subjects who ceased NPEP because their source was HIV‐uninfected. Results No participant became infected with HIV. For RAL‐FTC‐TDF and FTC‐TDF, regimen completion rates were 92% and 91% and medication adherence rates were 89% and 90%, respectively. Eight (9%) RAL recipients developed mild myalgias, with four developing transient grade 4 elevations in creatine kinase (two developed both), all of which improved to grade 2 or less by week 4 without RAL discontinuation. Eight prescribed and 37 potential illicit drug interactions with a protease inhibitor were avoided by use of RAL. Conclusions RAL‐FTC‐TDF is well tolerated as NPEP, results in high levels of adherence and avoids potential drug−drug interactions. Patients and clinicians should be aware of the potential for acute muscle toxicity when RAL is used as NPEP.